Den nya kvinnan behöver den nye mannen. Konstruktion av manliga identiteter i "Fru Marianne" av Victoria Benedictsson och "Dotter till en dotter" av Inger Alfvén - Szymoniak, Katarzyna (Versita, 2012)
The purpose of this paper is to problematize and compare the construction of masculine identity in two Swedish novels, Fru Marianne (1887) by Victoria Benedictsson and Dotter till en dotter (1977) by Inger Alfvén. The analysis is focused on how the male characters in these novels are constructed in the light of masculinity studies. In order to do that two types of masculine identity are considered: the New Man and hegemonic man. In both novels a change of the masculine identity pattern from the hegemonic masculinity towards the identity of the New Man can be observed, even though this process is performed differently. In the construction of male protagonists both authors refer to the same materialistic and symbolic attributes, however, these attributes are valued differently and play a different role in construction of masculine identity. In construction of the masculine identity Benedictsson combines the attributes of the New Man with the positive features of the hegemonic man, whereas Alfvén rejects the hegemonic masculinity as oppressive and constructs the male protagonist as the New Man.
The New Woman Requires the New Man. Construction of Masculine Identity in "Fru Marianne" by Victoria Benedictsson and "Dotter till en dotter" by Inger Alfvén
Keywords: Benedictsson; Alfvén; Maskulinitet i litteratur; Den Nye Mannen i litteratur; Hegemonisk maskulinitet; Maskulinitetsforskning; Masculinity in literature; The New Man in literature; Hegemonic masculinity; Masculinity studies